2018
DOI: 10.26803/ijlter.17.8.2
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Teachers’ Uses and Perceptions of Interactive Whiteboards for Instruction

Abstract: This research examines several public school teachers' perceptions and usage of interactive whiteboards (IWBs). The study was conducted using the conceptual framework of Roger's (2003) theory of diffusion and innovation, Davis' (1989) technology acceptance model and Ajzen's (1991) theory of planned behavior. Nine public school elementary teachers who used IWB technology in their classrooms for a full academic year were selected as the participants for this research study. The data were collected using two int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…This is to meet 21st century learning that require teachers to bring them forward and adapt to the new educational standards and techniques. IS entails student centred learning where teachers play the role of facilitators and resource persons to provide students the opportunities to engage themselves (Samsonova, 2018). However, there are challenges for teachers to use IS in their lesson as revealed in our findings.…”
Section: Conclusion and Recommendationmentioning
confidence: 77%
“…This is to meet 21st century learning that require teachers to bring them forward and adapt to the new educational standards and techniques. IS entails student centred learning where teachers play the role of facilitators and resource persons to provide students the opportunities to engage themselves (Samsonova, 2018). However, there are challenges for teachers to use IS in their lesson as revealed in our findings.…”
Section: Conclusion and Recommendationmentioning
confidence: 77%
“…Consequently, the researcher suggested the development of resources such as ready-made lessons and websites where teachers could download and post lessons to support the integration of IWBs into classrooms. Other similar findings were: (a) using IWB for differentiated learning since several learning styles can be addressed incorporating IWBs (Samsonova 2018;2019); (b) incorporating classroom management software in teaching (Samsonova, 2018); and (c) using IWBs for whole and small group interactions (Mellingsaeter & Bungum, 2015). IWBs might help to minimise teachertalking time, improving some student skills such as discussions and teamwork (Arpacık, Kurşun, & Göktaş, 2018).…”
Section: Iwbs Applications In Classroomsmentioning
confidence: 84%
“…However, educators with more than 15 years of experience hold firmer positive beliefs than teachers with five years of experience. Lecturers holding higher degrees, such as MA or Ph.D., tend to have more positive thoughts toward IWBs and use them more frequently than educators with lower education levels (Samsonova 2018;2019). It has been found that some teachers experienced problems related to a lack of pedagogical knowledge, issues with technical skills, and access to materials required for efficient IWB use (Korkmaz &Cakil, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations